A Novel RGD-4C-Saporin Conjugate Inhibits Tumor Growth in Mouse Models of Bladder Cancer - Zuppone, Stefania; Assalini, Chiara; Minici, Claudia; Botrugno, Oronza A.; Curnis, Flavio; Degano, Massimo; Corti, Angelo; Montorsi, Francesco; Salonia, Andrea; Vago, Riccardo (Frontiers in Oncology, 2022)
Although toxin may have some advantages compared chemotherapeutic drugs in cancer therapy, e.g. a potent cytotoxic activity and a reduced risk of resistance, their successful application in the treatments to solid tumors still remains to be fully demonstrated. In this study, we genetically modified the structure of the plant-derived single-chain ribosome inactivating protein saporin (SAP) by fusing its N-terminus to the ACDCRGDCFCG peptide (RGD-4C), an αv-integrin ligand, and explored the anti-tumor activity of the resulting protein (called RGD-SAP) in vitro and in vivo, using a model of muscle invasive bladder cancer. We found that the RGD-4C targeting domain enhances the cytotoxic activity of SAP against various tumor cell lines, in a manner dependent on αv-integrin expression levels. In a subcutaneous syngeneic model of bladder cancer, RGD-SAP significantly reduced tumor growth in a dose-dependent manner. Furthermore, systemic administration of RGD-SAP in combination with mitomycin C, a chemotherapeutic drug currently used to treat patients with bladder cancer, increased the survival of mice bearing orthotopic bladder cancer with no evidence of systemic toxicity. Overall, the results suggest that RGD-SAP represents an efficient drug that could be exploited, either alone or in combination with the state-of-the-art therapies, for the treatment of bladder cancer and, potentially, of other solid tumors.